The Use of Hedges in Editorials in the Jakarta Post (Universitas Negeri Semarang, 2021)
Hedges are important in the newspaper, and the use of hedges in Editorial has been paid more attention. The purpose of this research was to investigate the use of hedges and explained how they work in Editorials in The Jakarta Post. The qualitative method was applied by using discourse analysis. The data were taken from Editorials of The Jakarta Post issued between October 6th, 2022 and December 28th, 2022 which highlighted political segments. The analysis was employed based on the taxonomy of Salager-Meyer (1997). The findings revealed that all seven types of hedges were used in The Jakarta Post's Editorials. However, among the seven hedges types, the modal auxiliary verbs were the most frequent hedge found in the editorials, comprising an approximate proportion of 73.91% of all hedges found in the editorials. Frequent utilization of modal auxiliary verbs was the typical writing style in The Jakarta Post newspaper. Further, the frequent utilization of modal auxiliary verbs was considered as the editorialist’s strategy to encourage the reader’s critical thinking